Copper Porphyrin Catalyzed C(sp3)–H Activation via Cross-Dehydrogenative Coupling: Facile Transformation of Aldehydes to Esters - Shan, Zi-Wei; Chen, Xiao-Yan; Zhang, Hao; Liu, Hai-Yang; Yuan, Gao-Qing (Synlett, 2022)
Copper porphyrin catalyzed alkane C–H bond functionalization with aldehydes via cross-dehydrogenative coupling (CDC) using DTBP oxidant has been firstly described in nonsolvents or nonadditives system. Different aryl/heteroaryl carboxylic esters were obtained in good to excellent yields depending on the aldehyde derivatives. This CDC reaction catalyzed by copper porphyrin has the advantages of shorter reaction time, lower reaction temperature, and catalyst loading as well as the aerobic reaction atmosphere.
Keywords: copper porphyrin; aldehydes; alkanes; cross-dehydrogenative coupling; C–H activation